COLLABORATIVE WRITING: PRODUCT AND STUDENTSâ REFLECTIONS - Wulandari, Fitri (JURNAL SMART, 2017)
Producing a jointly written text becomes popular investigation in some studies.Â  The main concern of the study was to investigate the studentsâ writing product and studentsâ reflection in collaborative writing. The study was mixed-method research with the exploratory design.Â  49 third year students at English Education Department in the academic year of 2016-2017 of STKIP Muhammadiyah Pringsewu Lampung attended the study.Â Â  The study compared texts produced by pairs with those produced by individual learners as the sources of quantitative data and the studentsâ reflection as qualitative data. The study also elicited the learners âreflections on the experience of collaborative writing. The study found that the studentsâ writing score that work in pairs/collaboratively was higher than individual work product. Writing collaboratively also give positive impact on the studentsâ social aspect. They learned to work in team and reduced their feeling of under pressure.